Views of Erbil interns on the adequacy of undergraduate clinical skills training - Hassan, Maaroof Tahseen; Hamad, Othman Arab; Ismael, Sherzad Ali (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: One of the fundamental aims of all medical schools is to ensure that medical graduates are prepared to start work safely as junior doctors. The transition of medical students to junior doctors has long been considered a primary practice of passage. In Iraqi Kurdistan Region, a two year internship (residency) is mandatory for medical graduates’ registration as practitioner doctors. This study aimed to determine the perceptions of Erbil intern on whether undergraduate clinical skills training adequately prepared them for internship responsibilities. Methods: This descriptive cross-sectional analytical study included 369 interns working in the public hospitals of Erbil Governorate. A questionnaire including two sections: the first is interns’ demographic characteristics and the second is their views on clinical skills training (communication and practical). The collected data was analyzed by the statistical package for the social sciences (version 19.1). Results: Out of the 369 interns, 213 were filled the questionnaire. The majority of them felt that their undergraduate communication skills training were adequate in all the studied areas. However, more than half of the respondents felt that undergraduate practical skills training were inadequate in several areas. Female interns felt that training was adequate in all areas of communication and practical skills more than males with a statistical difference in female catheterization (P <0.001). Interns of <30 years old felt that they received more than adequate training in both areas of communication and practical skills than those of ≥30 years old with a significant difference in interviewing patients (P = 0.047), measuring blood pressure (P = 0.023), Pap smear (P = 0.043), and resuscitation - basic cardiopulmonary resuscitation (P = 0.001). Conclusion: This study suggests that there are deficiencies in undergraduate practical skills training particularly in specific areas. Deficiencies presented by the interns should be considered and addressed. In-depth studies are required to identify ways to improve training.